2010
DOI: 10.1016/j.ijantimicag.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of daptomycin combined with rifampicin for the treatment of experimental meticillin-resistant Staphylococcus aureus (MRSA) acute osteomyelitis

Abstract: Daptomycin exhibits rapid bactericidal activity against Gram-positive organisms, including meticillin-resistant Staphylococcus aureus (MRSA). Daptomycin in combination with rifampicin needs to be assessed in bone infection. An MRSA acute osteomyelitis model was used. Daptomycin and vancomycin were compared, alone or in combination with rifampicin, over 4 days. Surviving bacteria were counted in bone, bone marrow and joint fluid. Vancomycin and daptomycin as single therapies were ineffective, but both combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 18 publications
4
34
0
2
Order By: Relevance
“…Published reports on the combination of DAP and FOF are few and have not addressed the effect of FOF on DAP resistance development (6,31,33). More data are available on the addition of RIF, which has been shown previously to delay the emergence of DAP resistance (12,20) and can significantly enhance clearance of complex MRSA infection when given in combination with DAP (1,38), possibly by suppressing the emergence of resistance to both agents (15). Combination therapy with DAP ϩ CLR has been shown to be superior to either antibiotic alone in the eradication of biofilms (29), but there have been no reports of macrolide antibiotics suppressing the emergence of DAP resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published reports on the combination of DAP and FOF are few and have not addressed the effect of FOF on DAP resistance development (6,31,33). More data are available on the addition of RIF, which has been shown previously to delay the emergence of DAP resistance (12,20) and can significantly enhance clearance of complex MRSA infection when given in combination with DAP (1,38), possibly by suppressing the emergence of resistance to both agents (15). Combination therapy with DAP ϩ CLR has been shown to be superior to either antibiotic alone in the eradication of biofilms (29), but there have been no reports of macrolide antibiotics suppressing the emergence of DAP resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and animal infection models have shown additive or synergistic effects with DAP combination therapy (29,42,44). Previous work has examined the effect of combination exposures on the emergence of DAP resistance, although these studies are often limited by a number of factors, including short exposure duration, use of static antibiotic concentrations, testing of reference strains rather than clinical isolates, and the small number of combinations examined (4,20,35,38). Of note, Entenza and colleagues demonstrated that beta-lactam antibiotics significantly decrease the emergence of DAP resistance during a week-long subinhibitory exposure in Gram-positive isolates from a laboratory collection.…”
mentioning
confidence: 99%
“…Combination therapy avoids the development of resistance to daptomycin [110]. Combination therapy should therefore have potential in patients with endocarditis, undrainable abscesses and other high-inoculum infections.…”
Section: Combination Therapy With Daptomycinmentioning
confidence: 99%
“…Second, daptomycin has a high and very rapid concentration-dependent bactericidal activity (8)(9)(10)(11), not affected by decreased susceptibility to vancomycin (12). Third, daptomycin shows an antimicrobial activity in an in vivo model of acute osteomyelitis (13) and penetrates rapidly into biofilms (14,15); also, due to its unique mechanism of action on cell membrane, daptomycin retains antimicrobial activity against both stationary-phase cultures of staphylococci within the biofilm and bacteria in the multiplication phase (16)(17)(18)(19)(20). Finally, the safety and tolerability of daptomycin have been established (21)(22)(23).…”
mentioning
confidence: 99%